Sex differences in marathon running with advanced age: physiology or participation? - Hunter, S. K.; Stevens, A. A. (Medicine & Science in Sports & Exercise, 2013)
The sex difference in marathon performance increases with age and place of the finisher, even at the elite level. Sociological factors may explain the increased sex gap, but there is limited empirical evidence for specific factors.